Atypical Anterior Optic Neuritis Resembles Anterior Ischemic Optic Neuropathy : A Unique Case Report - Kristian Goenawan; Indra Tri Mahayana; Tatang Talka Gani; Hartono Hartono (Majalah Oftalmologi Indonesia, 2017)
Purpose : We present a unique case of atypical anterior optic neuritis resemble anterior ischemic optic neuropathy Methods : This was a single case study, with a patient was followed up for 2 months. Visual acuity, visual field, color vision, intraocular pressure, and ocular anatomy, were examined. Results : A female patient 54 y/o with chief complain sudden blurred vision on both eyes after woke up in the morning without redness and tearing 4 days before day of visit. History of systemic and ocular diseases were denied. Visual acuity was 0.5/60 (superior) right eye and 1/60 (superior) left eye, couldn’t be corrected. Relative afferent pupillary defect was observed in right eye. Biomicroscopic examination of anterior segment and intraocular pressures were normal. Funduscopy revealed ill defined margin at optic nerve head for both eyes suggested papilledema. At the present we couldn’t examined color vision. Visual field examination showed inferior altitudinal defect (more severe in right eye). Consultation to internal medicine and laboratory examination such as: complete blood count, lipid profile, blood glucose, and electrocardiogram were done to confirm our diagnosis. Clinically, the diagnosis of the disease more likely to be the anterior optic neuritis. Follow-up after 2 months has normal visual acuity, visual field, and color perception after steroid treatment. Conclusion : Anterior optic neuritis might have a very similar clinical presentation of anterior ischemic optic neuropathy upon early manifestation.